(untitled) (Quinto Sol, 2017)
This article analyses the book written by Reynaldo Pastor and entitled Frente al totalitarismo peronista as a late result of antiperonista literature. The mentioned text exposes the mixing of a liberal-conservative antifascist tradition with a renewed anti-totalitarian Cold War preaching. In this work, we indicate the importance of the role that political taxonomy played as a way to make believable the idea of consistency between peronismo and totalitarianism. As a novelty, it can be noted the use of a two-columns design in the strategy of the author of the reported book to confirm the identity between peronismo and communism.